Solar Powered Water Management System Using Smart Card (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With rapid development of economy and urban growth, water shortage and resource pollution is now a serious problem for urban water supply in many cities. At same time, with enlargement of urban areas and increase of sealing areas results in reduction of green spaces, new road and building construction etc., runoffs of rainwater increase greatly. Networked, smarts systems will help make enhanced use of energy, avoid superfluous and water losses and lessen the consumption of resources. In addition to automation and drive technology, this paper introduce solar powered drinking water supply management using RFID technology. In this paper RFID technology is used to manage the supply of water to the people, if the RFID card is placed near to the RFID reader, LCD displays the details regarding that card holder. According to the details, the DC Motor will pump the water and the message will be sent to the card holder regarding the water consumed